The Development of a Child Safety Bike With an Iot-Based Accident Detection System, Monitoring Camera, GPS Tracking Device, and SMS Notification: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
AbstractRiding a bike is a great way for children to stay active and explore the world around them.However, safety concerns have become a growing issue for parents and guardians. Thisstudy aims to address this issue by developing a child safety bike with various safety features,including an IoT-based accident detection system, monitoring camera, GPS tracking device,and SMS notification. These safety features are designed to increase child safety while ridingbikes by providing parents and guardians with real-time updates on their child's location, anyaccidents or collisions, and live video footage.The prototype's design, schematic diagram, and control system were implemented andanalyzed. The accident detection system uses an accelerometer sensor to detect suddenchanges in motion, and the GPS tracking device provides real-time location updates. TheSMS notification system alerts parents or guardians if their child deviates from apredetermined route. However, if a child does not have an accident but presses the button fora false alarm/accident, the SMS alert will not be received by the guardians or parents. Formonitoring, the FTDI adapter was used to connect the ESP32 module camera to captureimages and live video footage of the rides and notify parents or guardians in real time. Theresearchers found that the technologies used, including the IoT-based accident detectionsystem, monitoring camera, GPS tracking device, and SMS notification feature, werecompatible with each other. The prototype was functional and successful, as confirmed by thepositive feedback from the respondents regarding the efficiency, durability, safety, andeconomy of the prototype. The researchers concluded that the use of these technologies inthe development of the prototype is effective in creating a child-safety bike.In summary, the development of a child safety bike with an IoT-based accident detectionsystem, monitoring camera, GPS tracking device, and SMS notification is an innovativesolution to the growing safety concerns of parents and guardians. The prototype developed inthis study shows promising results in improving child safety during bike rides. This researchcontributes to the throwing field of IoT and promotes child safety in outdoor activities.
Keywords: Engineering; Computer Science